The Effect of Dynamic Capabilities and IT Capability on Firm Performance Perspective Mediating by Digital Transformation in Small Medium Enterprise (International Journal of Scientific Research and Management (IJSRM), 2021)
The purpose of this study is to determine the effect of information technology capabilities and dynamic capabilities on company performance which is moderated by digital transformation. The research approach used is quantitative with the type of survey research. The population in this study were small and medium enterprises (UKM) in the manufacturing sector in Surakarta which were registered in the database of the Surakarta Cooperative and UMKM Office with a sample of 100 SMEs with the unit of analysis being the owners of MSMEs. Data analysis was performed by conducting data quality tests and hypothesis testing using PLS (Partial Least Square). The results of the study concluded that information technology capabilities and dynamic capabilities have an influence on company performance through digital transformation.